CTNI-12. PRELIMINARY RESULTS OF THE ABEMACICLIB ARM IN THE INDIVIDUALIZED SCREENING TRIAL OF INNOVATIVE GLIOBLASTOMA THERAPY (INSIGHT): A PHASE II PLATFORM TRIAL USING BAYESIAN ADAPTIVE RANDOMIZATION. (9th November 2020) - Wen, Patrick; Trippa, Lorenzo; Lee, Eudocia; Fell, Geoffrey; Rahman, Rifaquat; Arrillaga-Romany, Isabel; Touat, Mehdi; McCluskey, Christine; Brunno, Jennifer; Gaffey, Sarah; Drappatz, Jan; Lassman, Andrew; et al.
Abstract: BACKGROUND: The cyclin D-CDK4/6-Rb pathway is activated in most glioblastomas. Abemaciclib is a potent CDK4/6 inhibitor with good brain penetration approved for ER/PR/HER2- breast cancer. In order to efficiently evaluate the potential impact of abemaciclib on overall survival (OS) in newly diagnosed glioblastoma and to simultaneously develop information regarding potential genomic biomarker associations, abemaciclib was included as an arm on the Individualized Screening Trial of Innovative Glioblastoma Therapy (INSIGhT) trial. INSIGhT is a phase II platform trial using response adaptive randomization and deep genomic profiling to more efficiently test experimental agents in MGMT unmethylated glioblastoma and potentially accelerate identification of novel therapies for phase III testing. Initial randomization was equal between abemaciclib, control, and two other experimental arms but subsequent randomization was adapted based on efficacy as determined by progression-free survival (PFS). Ineffective arms were discontinued and new arms added by protocol amendment. We report preliminary results for the abemaciclib arm which has completed accrual. METHODS: Patients with newly diagnosed MGMT-unmethylated glioblastoma were randomized to receive either radiotherapy with concomitant and adjuvant temozolomide at standard doses or standard radiochemotherapy followed by adjuvant abemaciclib (150–200 mg orally BID) without temozolomide. Treatment continued until progression or development of unacceptable toxicities. The primary endpoint was OS. Association between abemaciclib efficacy and cyclin D-CDK4/6-Rb pathway genomic alterations was also investigated. RESULTS: There were 123 patients (50 control; 73 treated with abemaciclib). Abemaciclib was generally well-tolerated with no new toxicity signals identified. PFS was significantly longer (p=0.03, logrank test) with abemaciclib (median 6.31 months 95% CI [5.29, 8.18]) compared to the control arm (5.16 months 95% CI [4.37, 6.28]). 28/50 control and 36/73 abemaciclib patients remain alive. CONCLUSION: Preliminary analysis suggests that abemaciclib increases PFS compared to control. Updated toxicity, PFS and survival data and potential genomic biomarker associations will be presented.